PENGARUH LAMA FERMENTASI TERHADAP KUALITAS SUSU TEMPE BUBUK SEBAGAI PENGEMBANGAN LKM (LEMBAR KERJA MAHASISWA) MATERI BIOTEKNOLOGI PANGAN - Imam Mahadi; Darmawati "; Apriyani " (Biogenesis, 2016)
ABSTRACT The aims of this research to determine the quality of tempeh milk powder by time fermentation and designing Student Worksheet relevant to a material Food Biotechnology Food Fermentation sub material. This study consisted of two phases. The first phase, were the making of  tempeh milk powder using the experimental method with completely randomized design (CRD), which consists of 5 treatments and 3 replications. Parameters measured were moisture content, protein content, fat content, pH and organoleptic test. The results obtained were analyzed by ANOVA and a further test DMRT at 5% level. The second phase were the development of  Student Worksheet from the results of the first phase. This research used ADDIE development model (Analysis, Design, Development, Implementation and Evaluation) are simplified into phases Analysis, Design and Development. Data of Student Worksheet development obtained from the validation sheet which validated by 3 validators with 5 validity criterias were analyzed descriptively. Results showed that the time of fermentation influence on moisture content, protein content, fat content, pH and organoleptic test. Fermentation time 12 hours is a long time to produce the best fermented tempeh milk powder quality. Which results in moisture content of 0.78%, 2.61% protein content, fat content 2.00% and 5.01 pH levels. As for organoleptic texture, color, aroma and flavor contained in the fermentation 36 hours. Results of the study can be used as Student Worksheet in the sub materials Food Fermentation on the material Food Biotechnology with a mean value of 3.32 validity valid category. Keywords : Student Worksheet, Food Biotechnology, Tempeh Milk Powder, Time Fermentation.